Pengembangan Multimedia Interaktif pada Materi Listrik untuk Siswa Kelas IX SMP: The Development Of Interactive Multimedia On Electrical Material for IX Graders In Junior High School - Ranti Erfiana; Maison Maison; M. Haris Effendi Hsb (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2020)
The background of this research is dependence the learning process by students to teachers and the lowers score of physics. There is some factors of that such as students can not doing independent study and the less of material in the school. The purpose of this research and development find out expediency the develop, practice and effective of interactive multimedia. This research and development using ADDIE models develop design. The technique of collecting the data by using questionnaire and multiple choice question. The analysis technique of this research using qualitative and quantitative method. Based on the results of validation develop multimedia doing by expert are valid and can be trying, while the result of response of the teacher got 90,7% in the excellent category, the result of response of the students try out one by one got 92,44% in the excellent category, the result of response of the students try out in a small group got 90,5% in the excellent category and the result roomy and effective try out got 58,96 in control class and 72,92 in experiment class.